2021
DOI: 10.5606/ehc.2021.77870
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radial extracorporeal shock wave therapy in post-laminectomy epidural fibrosis in a rat model

Abstract: Objectives This study aims to investigate the effect of radial extracorporeal shock wave therapy (rESWT) treatment in the prevention of epidural fibrosis after laminectomy in rats. Materials and methods Eighteen 16-month-old male Sprague-Dawley rats weighing 300 g were used in this experimental study between November 2019 and February 2020. The rats were randomly divided into two groups as the control group (L3-L4 total laminectomy without any treatment) and the study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…We have not studied the mechanisms involved in the reduction of interstitial collagen between muscle fibers after MAP therapy. Nevertheless, low-intensity extracorporeal shock wave therapy (Li-ESWT)-induced reduction of collagen fibers in liver fibrosis and spine surgery has been attributed to modulation of the TGFsignaling pathway and matrix metalloproteinases (46,47). Our current study is the first to examine the biomechanical effects of MAP on the PFM after simulated birth injury.…”
Section: Discussionmentioning
confidence: 94%
“…We have not studied the mechanisms involved in the reduction of interstitial collagen between muscle fibers after MAP therapy. Nevertheless, low-intensity extracorporeal shock wave therapy (Li-ESWT)-induced reduction of collagen fibers in liver fibrosis and spine surgery has been attributed to modulation of the TGFsignaling pathway and matrix metalloproteinases (46,47). Our current study is the first to examine the biomechanical effects of MAP on the PFM after simulated birth injury.…”
Section: Discussionmentioning
confidence: 94%
“…It is also a safe and effective non-invasive treatment for many fibrotic diseases such as myogenic contracture, pathological scars, epidural fibrosis, etc. [13][14][15][16][17][18][19][20]. In this study, extension knee joint contracture in rats was treated in different ways, to explore whether the treatment effect of SPS combined with ESWT is better than single treatment, and to guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that ESWT can reduce cell migration and effectively inhibit the expression of TGF-β1, alpha smooth muscle actin (α-SMA), type I collagen, and fibronectin [ 16 ], making it a feasible and cost-effective method for the treatment of pathological scars after burns [ 17 ]. In addition, ESWT can significantly and effectively reduce the fibrosis in the treatment of epidural fibrosis [ 18 ] and capsular fibrosis after insertion of silicone implants [ 19 ]. Huang et al [ 13 ] found that radial ESWT combined with ultrashort wave therapy could inhibit the high expression of TGF-β1 and hypoxia-inducible factor 1 alpha (HIF-1α), and radial ESWT could inhibit the NF-κB/HIF-1α signaling pathway [ 14 ], which could reduce the myogenic contracture after long-term immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…More intriguingly, in an experimental study of rats with spinal cord damage, low-energy ESW application increased angiogenesis by increasing vascular endothelial growth factor expression in nerve cells, thus improving locomotor and sensory functions. [ 37 ] Finally, in an in vivo study, Haberal et al[ 38 ] reported that shock wave therapy applied in rats with lumbar laminectomy reduced epidural fibrosis. The reason for the decrease in epidural fibrosis in this study may be the fibroblast death due to the genotoxic damage observed in the current study, and the possible effect of inflammation triggered by this cytotoxic effect on wound healing.…”
Section: Discussionmentioning
confidence: 99%